Characterization of Key Aroma Compounds in Xiaoqu Liquor and Their Contributions to the Sensory Flavor - Zhe Wang; Xizhen Sun; Yuancai Liu; Hong Yang (Beverages, 2020)
The objective of this study was to investigate the aroma profile and major flavor compounds in Xiaoqu liquor by a combination of sensory profiling, GC-O/GC-MS analysis, and SBSE-GC-MS. A total of 57 important volatile compounds (FD ≥ 2) were screened based on the retention indices, aromatic characteristics, standard comparison, and aroma extract dilution analysis (AEDA). By calculating the odor activity values (OAVs), 32 aroma active compounds were identified in Xiaoqu liquor. In the aroma recombination experiments, these active compounds were dissolved in 46% ethanol water at their natural concentrations, resulting in successful simulations of the typical aromas of Xiaoqu liquor, including fruity aroma, sweet aroma, and grain aroma. Omission experiments showed that the critical compounds that contribute to the characteristic flavor of Xiaoqu liquor include ethyl octanoate, acetaldehyde, 1,1-diethoxyethane, isoamyl acetate, ethyl acetate, valeric acid, 1-octen-3-ol, and ethyl isovalerate. The results provide some guidance for upgrading the fermentation and microbial strain in the production of Xiaoqu liquor.